Pentingnya Peningkatan Gizi Anak Berbasis Pangan Lokal - Gordianus Pratama Baho; Indriyati Indriyati; Hendrikus L. Kaha; Frans Nyong; Yasinta P. Peten; Stephanie P.A Lawalu; Marianus kleden; Alfry Silae (Universitas Kristen Indonesia Toraja, 2024)
The local-based program to improve nutrition for children is one of the efforts to strengthen families by maintaining local-based food security. This program aims to increase family knowledge and skills regarding the use of land or home gardens by planting local plants that contain high nutrients and processing locally based food ingredients. The program implementation method involves identifying the potential of village community land, identifying problems, socializing and training on desert management based on local fruit. The results of implementing the community work program can process local food ingredients and fruit into food menus that can improve children's nutrition, understand the nutritional content of local fruit, and prepare land for planting local fruit. Indirectly, this program can be useful in increasing the knowledge of mothers and childrasn initial step in preventing stunting.